Melanocortin 1 Receptor: Structure, Function, and Regulation - Wolf Horrell, Erin M.; Boulanger, Mary C.; D’Orazio, John A. (Frontiers in Genetics, 2016)
The melanocortin 1 receptor (MC1R) is a melanocytic Gs protein coupled receptor that regulates skin pigmentation, UV responses, and melanoma risk. It is a highly polymorphic gene, and loss of function correlates with a fair, UV-sensitive, and melanoma-prone phenotype due to defective epidermal melanization and sub-optimal DNA repair. MC1R signaling, achieved through adenylyl cyclase activation and generation of the second messenger cAMP, is hormonally controlled by the positive agonist melanocortin, the negative agonist agouti signaling protein, and the neutral antagonist β-defensin 3. Activation of cAMP signaling up-regulates melanin production and deposition in the epidermis which functions to limit UV penetration into the skin and enhances nucleotide excision repair, the genomic stability pathway responsible for clearing UV photolesions from DNA to avoid mutagenesis. Herein we review MC1R structure and function and summarize our laboratory’s findings on the molecular mechanisms by which MC1R signaling impacts nucleotide excision repair.